A PRELIMINARY STUDY ON THE RESPONSE OF AMPHIPHOD GRANDIDIERELLA SP. TO CONTAMINATED SEDIMENT OF JAKARTA BAY - Hindarti, Dwi; Puspitasari, Rachma; Arifin, Zainal (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2010)
A preliminary study on the response of amphipod exposed to contaminated sediments of Jakarta Bay was carried out in October 2009. The objective of the study was to determine the mortality rate of amphipod in response to exposure of contaminated sediments. Seven sediment samples were taken from the bay, i.e, reference site (St. A), and six-contaminated sites (St. B3, B5, C3, C5, D3, and D5). Amphipod (Grandidierella sp.) was collected from reference site. The study showed that average of mortality rate of amphipod ranged between 50.0 and 76.3% at contaminated sediments and 38.3% at reference sediments. There was significant difference on mortality rate of amphipod exposed to sediments of reference site and that of contaminated sites. The mortality of Grandidierella sp. was not strongly correlated with the concentration of Pb and Cu in contaminated sediments. The critical mortality factor of amphipod in this study might be due to variation in grain size of sediments and short period of acclimatization.